Anti-Müllerian hormone in African-American women with systemic lupus erythematosus - S Sam Lim; Meghan Angley; Jessica B Spencer; Penelope P Howards (Lupus Science and Medicine)
Objective Women with SLE may experience ovarian insufficiency or dysfunction due to treatment or disease effects. Anti-Müllerian hormone (AMH), a marker of ovarian reserve, has been examined in small populations of women with SLE with conflicting results. To date, these studies have included very few African-American women, the racial/ethnic group at greatest risk of SLE.Methods We enrolled African-American women aged 22–40 years diagnosed with SLE after age 17 from the Atlanta Metropolitan area. Women without SLE from the same area were recruited from a marketing list for comparison. AMH was measured in serum using the Ansh Labs assay (Webster, Texas, USA). We considered AMH levels <1.0 ng/mL and AMH <25th percentile of comparison women as separate dichotomous outcomes. Log-binomial regression models estimating prevalence ratios were adjusted for age, body mass index and hormonal contraception use in the previous year.Results Our sample included 83 comparison women without SLE, 68 women with SLE and no history of cyclophosphamide (SLE/CYC−) and 11 women with SLE and a history of cyclophosphamide treatment (SLE/CYC+). SLE/CYC+ women had a greater prevalence of AMH <1.0 ng/mL compared with women without SLE (prevalence ratio (PR): 2.90, 95% CI: 1.29 to 6.51). SLE/CYC− women were also slightly more likely to have AMH <1.0 ng/mL (PR: 1.62, 95% CI: 0.93 to 2.82) than comparison women. Results were similar when considering AMH <25th percentile by age of comparison women.Conclusions Treatment with CYC is associated with low AMH in African-American women with SLE. SLE itself may also be associated with reduced AMH, but to a lesser extent.